Short Intracortical Inhibition During Voluntary Movement Reveals Persistent Impairment Post-stroke - Ding, Qian; Triggs, William J.; Kamath, Sahana M.; Patten, Carolynn (Frontiers in Neurology, 2019)
Objective: Short intracortical inhibition (SICI) is a GABAA-mediated phenomenon, argued to mediate selective muscle activation during coordinated motor activity. Markedly reduced SICI has been observed in the acute period following stroke and, based on findings in animal models, it has been posited this disinhibitory phenomenon may facilitate neural plasticity and contribute to early motor recovery. However, it remains unresolved whether SICI normalizes over time, as part of the natural course of stroke recovery. Whether intracortical inhibition contributes to motor recovery in chronic stroke also remains unclear. Notably, SICI is typically measured at rest, which may not fully reveal its role in motor control. Here we investigated SICI at rest and during voluntary motor activity to determine: 1) whether GABAA-mediated inhibition recovers, and 2) how GABAA-mediated inhibition is related to motor function, in the chronic phase post-stroke. Methods: We studied 16 chronic stroke survivors (age: 64.6±9.3 years; chronicity: 74.3±52.9 months) and 12 age-matched healthy controls. We used paired-pulse transcranial magnetic stimulation to induce SICI during three conditions: rest, submaximal grip, and performance of box-and-blocks. Upper-extremity Fugl-Meyer Assessment and Box-and-Blocks tests were used to evaluate motor impairment in stroke survivors and manual dexterity in all participants, respectively. Results: At rest, SICI revealed no differences between ipsilesional and contralesional hemispheres of either cortical or subcortical stroke survivors, or healthy controls (P’s>0.05). During box-and-blocks, however, ipsilesional hemisphere SICI was significantly reduced (P=0.025), especially following cortical stroke (P<0.001). SICI in the ipsilesional hemisphere during box-and-blocks test was significantly related to paretic hand dexterity (r=0.56, P=0.039) and motor impairment (r=0.56, P=0.037). Conclusions: SICI during motor activity, but not rest, reveals persistent impairment in chronic stroke survivors indicating that inhibitory brain circuits responsible for motor coordination do not fully normalize as part of the natural history of stroke recovery. Observation that reduced SICI (i.e., disinhibition) is associated with greater motor impairment and worse dexterity in chronic hemiparetic individuals suggests the response considered to promote neuroplasticity and recovery in the acute phase could be mladaptive in the chronic phase post-stroke.